Examining Indonesia's Preparations for Ratifying the BBNJ Agreement - Noensie, Ardelia Clarissa; Prasetiyo, Putri Widhyastiti (Jurist-Diction, 2025)
The Biodiversity Beyond National Jurisdiction (BBNJ) Agreement is a crucial international legal instrument for conserving marine biological diversity in areas beyond national jurisdiction. Although Indonesia has signed the agreement, ratification has yet to be completed. This article aims to assess Indonesia's readiness to ratify the BBNJ Agreement. Through a normative-empirical approach, this article will analyze the relevance of the BBNJ Agreement to Indonesia, the ratification process for international agreements in Indonesia, and the progress of Indonesia's preparations to ratify the BBNJ Agreement. This article is expected to provide recommendations to policymakers to accelerate the ratification process and support Indonesia's contribution to the sustainable management of conserving marine biological diversity in areas beyond national jurisdiction.